Subjective experiences of tertiary student pianists with playing-related musculoskeletal disorder: a transcendental phenomenological analysis - Xiaoyu, Miao; Musib, Ahmad Faudzi; Selvarajah, Indra V. (Frontiers Media SA, 2024)
Background: The literature suggests that the medical community needs musicians to provide an insider’s perspective to understand the physical and psychological dimensions of playing an instrument, and healthcare providers need to understand musicians’ experiences in order to develop coping strategies. Compared with professional pianists, student pianists are a neglected group. However, student and professional pianists both want to maintain their playing careers and have the experience of giving up playing because of playing-related musculoskeletal disorder (PRMD). There are a few studies conducted on student pianists’ experiences with PRMD, but none have been conducted in the Chinese context. Given the distinctive characteristics of higher music education in China and Chinese piano students, this study aims to investigate the lived experiences of tertiary student pianists with PRMD. Methods: Phenomenology is the most suitable qualitative method for investigating lived experiences. This study employed a transcendental phenomenological approach to investigate the experiences of student pianists, collecting data through one-on-one interviews and focus group discussions. Since phenomenological research emphasizes the homogeneity of research subjects, all 25 participants in this study are tertiary student pianists from seven Chinese higher education institutions. Results: Four themes and ten sub-themes were identified in this study. They are as follows: Theme one, Perceptions of PRMD, with sub-themes of body perceptions, negative thought, and emotional changes; Theme two, Complex Identity, with sub-themes of future pianists’ identity, nuanced identity of student pianists, and the dual identity between student pianist and patient; Theme three, Coping Strategies, with sub-themes of self-regulation and actively seek help from social relations; Theme four, Influences and Meanings, with sub-themes of negative influences of PRMD and positive meanings of PRMD. Conclusion: This study explores the experiences of tertiary student pianists with PRMD, including their subjective thoughts and feelings. It also highlights the importance of understanding tertiary student pianists’ experiences in developing health education and healthcare measures tailored to them.